Limiting clinical heterogeneity in schizophrenia : can affected Xhosa sib pairs provide valid subtypes? - Niehaus, Daniel Jan Hendrik (Stellenbosch : University of Stellenbosch, 2006)
Thesis (DMed (Psychiatry))--University of Stellenbosch, 2005.